2019
DOI: 10.12659/msm.915136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Correlation Between Age and Cervical Facet Joint Degeneration and Modic Changes in Patients with Cervical Spondylotic Myelopathy

Abstract: Departmental sources Background: Because facet joints move with the disc, changes in vertebral bodies occur simultaneously with progression of degeneration of cervical facet joints. This study investigated age-related differences in cervical facet joint abnormalities and multi-dimensional characteristics of MCs in patients with cervical spondylotic myelopathy. Material/Methods: Forty-five patients underwent both magnetic resonance imaging (MRI) and computed tomography (CT) of the cervical spine. Axial and sagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition, the cumulative effect of micro-injury can initiate or accelerate cervical degeneration. Significant Modic changes are a predisposing factor for facet degeneration [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cumulative effect of micro-injury can initiate or accelerate cervical degeneration. Significant Modic changes are a predisposing factor for facet degeneration [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the angles of the cervical facet joints were often measured only through 2-dimensional axial tomographic images on CT or Magnetic Resonance Imaging (MRI). 20 , 21 , 43 However, it is difficult to accurately describe the 3-dimensional orientation of the facet joint planes by drawing lines on the 2-dimensional images, especially considering the oblique position of the cervical facet joints. The 3-dimensional measurement method we used can divide tropism into 3 types: tropism with respect to the sagittal plane (sagittal tropism), tropism with respect to the coronal plane (coronal tropism), and tropism with respect to the transverse plane (transverse tropism).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we evaluated the relationship between degenerative spinal phenotypes and sagittal balance in patients with neck pain. While the relationship between MCs in the lumbar spine and FD is common in the literature, studies on the relationship between these changes in the cervical spine are scarce [ 5 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship of MCs with FD was examined, and no relationship was observed between FD and MCs at the same level of the cervical spine [ 7 , 8 , 17 ]. However, Lv et al showed that the size of MCs was related to cervical FD [ 5 ]. With this study, we have seen that MCs, FD, and DD at the same level of the cervical spine are interrelated with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation